Classroom Interaction: An Analysis of Teacher Talk in Moroccan EFL Classrooms. - RIAD, Jaouad (International Journal of Language and Literary Studies, 2023)
Classroom interaction has always been considered at the heart of the teaching-learning process since it allows students to deepen their comprehension of the course subject and improve their speaking skills. However, the previous studies denoted that teachers dominate when speaking in the classroom. Therefore, this study aims to analyze the nature of teacher talk along with the categories which are frequently used in the classroom based on the FLINT analysis system. The design of this research is descriptive qualitative. The sample of the study was 7 Moroccan secondary EFL teachers in Agadir. The data was gathered by naturalistic observation and recording. The data were processed using Moskowitz’s (1971) Foreign Language Interaction (FLINT) system. The findings confirmed teachers’ use all of the categories of teacher talk as mentioned in FLINT. However, the most often utilized categories were found to be giving direction and lecturing. Moreover, the teachers primarily assumed the role of controllers in the classroom, frequently leading the flow of engagement. The findings have a number of implications for Moroccan EFL secondary classrooms.